Keberadaan Boraks Pada Makanan Jajanan Di Kota Banjarbaru - M. Ilham Rusadi; Rahmawati Rahmawati; Erminawati Erminawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2016)
Abstract:  Boraks availability on food hawker at Banjarbaru city. Pentol bakso is a very popular food in Banjarbaru City. Almost all walks of life loved this dish because flavors are tasty and the prices are cheap so not surprised if traders bulb meatballs mushrooming in every area. To meet the standard that favored consumers save time and extend the bulb meatballs, many merchants are not responsible for adding chemicals that are actually prohibited from foods like boraks. This research aims to know the existence of boraks and factors which determine the presence of boraks on food hawker bulb meatballs sold around Field Murjani. The type of research used are descriptive i.e. describing the existence of boraks, level of knowledge, and merchant processing on food hawker pentol bakso sold around the field with the approach of cross sectional Murjani. The results of laboratory examination showed that all samples taken from the pentol bakso traders selling in the vicinity of the field there is no boraks Murjani. All merchants using only food additives are allowed in processing pentol bakso. It is supported most traders have a good knowledge about the food additives. The traders expected that pentol bakso still give priority to safety and security of consumers  economic interests above personally by not entering the banned food additives into processed food products. Keywords: Food snack, Boraks